Tissue-specific NETs alter genome organization and regulation even in a heterologous system. (2nd January 2017) - de las Heras, Jose I.; Zuleger, Nikolaj; Batrakou, Dzmitry G.; Czapiewski, Rafal; Kerr, Alastair R. W.; Schirmer, Eric C.
ABSTRACT: Different cell types exhibit distinct patterns of 3D genome organization that correlate with changes in gene expression in tissue and differentiation systems. Several tissue-specific nuclear envelope transmembrane proteins (NETs) have been found to influence the spatial positioning of genes and chromosomes that normally occurs during tissue differentiation. Here we study 3 such NETs: NET29, NET39, and NET47, which are expressed preferentially in fat, muscle and liver, respectively. We found that even when exogenously expressed in a heterologous system they can specify particular genome organization patterns and alter gene expression. Each NET affected largely different subsets of genes. Notably, the liver-specific NET47 upregulated many genes in HT1080 fibroblast cells that are normally upregulated in hepatogenesis, showing that tissue-specific NETs can favor expression patterns associated with the tissue where the NET is normally expressed. Similarly, global profiling of peripheral chromatin after exogenous expression of these NETs using lamin B1 DamID revealed that each NET affected the nuclear positioning of distinct sets of genomic regions with a significant tissue-specific component. Thus NET influences on genome organization can contribute to gene expression changes associated with differentiation even in the absence of other factors and overt cellular differentiation changes.